FEATURES OF IMPLEMENTATION OF THE PUBLIC CONTROL MECHANISM IN PUBLIC GOVERNANCE - Iuskov, G. (Theory and Practice of Public Administration, 2019)
It is stated that in the system of public relations in state bodies of power and management system-forming is a function of management, as the realization of a set of tasks subject to the main purpose of influence on public opinion, on corporate relations. It is emphasized that in the sphere of public relations the object and the subject of management have equal rights. One of the most important functions of public relations services of public authorities and government in a democratic state is the function of aggregation and articulation of public interests. In fulfilling this function, public relations services become a full participant in defining the goals of managerial influence, while becoming a kind of “public lawyer”, protecting and defending the interests of a particular consumer of services of a particular state body. In today’s society, there is a continuous process of production and circulation of messages between different elements of the political system and the political and social systems, aimed at achieving social consensus and ensuring the stable and efficient functioning of the political system in a democratic society. Political communication is one of the main functions of the political system, which in the conditions of the democratic and political regime requires regular confirmation of its legitimacy by other members of political society, and an indispensable condition for its existence. The functions of public relations services in relation to public and local authorities are related to the main task of public administration - the task of serving the society from which they were empowered. The tasks of the civil service in a democratic state are to ensure the most effective alignment of the interests of the governed and the governed, the state and the society, in a timely and adequate way to respond to emerging conflicts, seeking to anticipate and anticipate them in their work. Ensuring systematic interaction between government and the public is one of the most important requirements of governance in a democratic society. Thus, the study of PR, analysis of the features and trends of their development showed the need for the formation of public relations services as an institution, which communicates to the system of management needs and demands of society, informs it about the public response to public authorities and decision management, and, therefore, it changes the control system itself. Public relations services are those institutions that provide a continuous dialogue between state authorities and government and society, providing feedback, aggregating and articulating public interests, being complicit in the process of defining a goal in a particular state body. By participating in this process, public relations services of public authorities and administrations defend and protect public interests, thus implementing a constitutional course on the democratization of the state and society, which dictates the need to involve society in the decision-making process. The purpose of public relations and public relations services is to ensure systematic interaction between authorities and the public, to establish bilateral communication for the common interest and mutual understanding, to participate in state government targeting and to protect the public interest.